2021
DOI: 10.1007/s11666-021-01224-9
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Bond Formation in Polymer Surface Metallization Using Cold Spray

Abstract: Surface metallization of polymeric materials using cold spray technology has gained increasing attention in the past decade. Experimental studies have evidenced multiple challenges of this process regarding continuity and homogeneity of the metallic deposits on polymer substrates. Modeling and simulation tools could be very helpful to assess the efficiency of different strategies suggested for improved deposition at a considerably reduced cost; nevertheless, the efforts to use numerical modeling in this sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…The three-dimensional numerical model was introduced in our previous work [10], considering the only PEEK substrate. Here, only the main points are recalled, introducing the different implementations due to the composite.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-dimensional numerical model was introduced in our previous work [10], considering the only PEEK substrate. Here, only the main points are recalled, introducing the different implementations due to the composite.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…For a successful deposition, the starting and key point of the coating is the first layer which is dictated by the interlocking velocity. Our previous research [10] focused on the deformation of a single Copper particle, deposited onto polyether ether ketone (PEEK). It was shown numerically that for the mechanical interlocking, a velocity threshold exists below which the particle detaches from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the last few years, several computational models have been developed in order to predict the behaviour of a particle impacting a substrate, simulating the operating conditions of Cold Spray process [10][11][12]. However, as concerns the coating process applied to polymers and composites, to date the very few works have been published [13][14][15]. Nevertheless, it was not possible to develop a validated physical model to describe the phenomena occurring during the deposition of metallic particles on non-metallic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…These works showed that the particle velocity must be selected properly within a deposition window by tuning the processing parameters. In particular, for a successful deposition of the first metal-to-composite layer, corresponding to the beginning of the coating's growth, the velocity must be higher than the interlocking velocity of particles with the polymeric substrate, but lower than the erosion velocity of the polymer itself, as proved through experiments analyzing the whole coated layer [9,15] and the single-particle impact [16], as well as with complex numerical simulations [17,18].…”
Section: Introductionmentioning
confidence: 99%